Does the Central Corneal Thickness (CCT) retain its predictive value as a risk factor in Primary Open Angle Glaucoma patients with Diabetes Mellitus? - Khatri, Anadi; Khatri, Bal Kumar; Thapa, Madhu; Kharel, Muna; K.C., Ashma; Tmalsena, Satish (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: Central Corneal thickness (CCT) is thicker in diabetic patients. This may cause the CCT to lose predictive power as a risk factor for primary open angle glaucoma (POAG) in patients with diabetes. Objective: To evaluate if CCT of POAG patients with diabetes retains its predictive value as a risk factor. Methods: A cross sectional analysis of sequential group of patients with POAG with and without diabetes were evaluated HbA1C in diabetic patients and CCT in both groups was measured and the severity of POAG was evaluated using visual field changes and optic disc changes. The correlation was evaluated using confidence interval and liner regression estimator analysis. Results: Five hundred and eighty-seven patients with POAG were evaluated. The mean CCT for the group combined was 540±34.9 μm. Three hundred and thirty-seven patients had no history of diabetes and had mean CCT of 531.1±19.6 μm. Two hundred and fifty of them had diabetes with mean corneal thickness of 549±20.2 μm. CCT retained its predictive value as a risk factor for severity in POAG patient without diabetes (p<0.05). CCT however was a less sensitive for evaluating risk/severity in POAG patients with diabetes (p>0.05). Conclusions: CCT values may not retain its predictive value of severity of POAG in patients with diabetes. Hence, CCT alone may not be a reliable marker and mislead treating physicians.